Inducible expression of an antibiotic peptide gene in lipopolysaccharide-challenged tracheal epithelial cells. - Diamond, G (1996)
Mammals continually confront microbes at mucosal surfaces. A current model suggests that epithelial cells contribute to defense at these sites, in part through the production of broad-spectrum antibiotic peptides. Previous studies have shown that invertebrates can mount a host defense response characterized by the induction in epithelia] cells of a variety of antibiotic proteins and peptides when they are challenged with microorganisms, bacterial cell wall/membrane components, or traumatic injury [Boman, H.G. & Hultmark, D. (1987) Annu. Rev. Microbiol. 41, 103-126J. However, factors that govern the expression of similar defense molecules in mammalian epithelial cells are poorly understood. Here, a 13-fold induction of the endogenous gene encoding tracheal antimicrobial peptide was found to characterize a host response of tracheal epithelia] cells (TECs) exposed to bacterial lipopolysaccharide (LPS). Northern blot data indicated that TECs express CD14, a well-characterized LPS-binding protein known to mediate many LPS responses. A monoclonal antibody to CD14 blocked the observed tracheal antimicrobial peptide induction by LPS under serum-free conditions. Together the data support that CD14 of epithelial cell origin mediates the LPS induction of an antibiotic peptide gene in TECs, providing evidence for the active participation of epithelial cells in the host's local defense response to bacteria. Furthermore, the data allude to a conservation of this host response in evolution and suggest that a similar inducible pathway of host defense is prevalent at mucosal surfaces of mammals.